answer is -1 < x < 5
-|x - 2|+ 9 > 6
Rearrange the terms
-|x - 2| > 6 - 9
-|x - 2| > - 3
then divide both sides of the inequality by the co- efficient of variable
|x - 2| < 3
convert the absolute inequality to standard inequality
-3 <x - 2 < 3
separate compound inequalities into system of inequality
{x - 2}> -3
{x - 2 < 3}
Rearrange variable to the left side of the equation
x > -3 + 2
calculate the sum or difference
x > -1
x -2 < 3
Rearrange variable to the left side of the equation
x < 3 + 2
calculate the sum or difference
x < 5
x > -1 and x < 5
Find intersection
-1 < x < 5
Equations and inequalities are both mathematical sentences formed by relating two expressions to each other. In an equation, the two expressions are deemed equal which is shown by the symbol =. Where as in an inequality, the two expressions are not necessarily equal which is indicated by the symbols: >, <, ≤ or ≥.
learn more about inequality equation here :https://brainly.in/question/15934172
SPJ9
Step-by-step explanation:
Here
BC=P=10
AC=B=b
AB=H=15
then using fourmula
h^2= p^2+ b^2
b^2= 15×15 - 10× 10
b^2= 125
b=11.2
Let's solve for h
hx = 0.5x - 9
Step 1: Divide both sides by x.
hx/x = 0.5x - 9/ x
Answer = h = 0.5x - 9/ x
** x + 5 = 7
x = 2
** x + 5 = 9
x = 4
{2,4}
Answer:
Step-by-step explanation:
<u>Given</u>
<u>Substitute x with -3</u>
-
h(-3) = (-3)^-2 = 3^-2 = 9^-1 = 1/9